Electric characterization and conduction mechanism of multi-functional thin films for electronic devices - Keh, Chee Xuan (2015)
Recently, magnetoelectric multiferroics have attracted much spotlight in the field of memory devices due to the magnetoelectric effect compared to the conventional materials. In this final year project, the magnetoelectric multiferroic material Pb(Zr,Ti)O3-Pb(Fe,Ta)O3 (PZTFT) was studied. The PZTFT thin films were fabricated by milling, sintering, pulsed laser deposition (PLD) technique and sputtering technique. Verification of the quality of the films was done using X-ray diffraction (XRD) technique, Atomic Force Microscopy (AFM) and Reflection High-Energy Electron Diffraction (RHEED). The high quality films were studied intensively under various conditions. Conduction mechanisms were identified and polarization hysteresis loops were measured through experiment.